1980
DOI: 10.1007/bf00406415
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and Young's modulus of human skin in vivo

Abstract: The mechanical properties of the in vivo dermis were measured by means of a torque applied to the skin. The resulting deformation of 2-6 degrees, including the immediate and delayed visco-elastic components, as well as the relaxation were measured, and the raw values corrected for a constant skin thickness. The experiment performed on 138 individuals from 3 to 89 years old revealed a diminished elasticity and stretchability after the age of 30, associated with an increase in the visco-elastic component. The Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
344
6
6

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 633 publications
(397 citation statements)
references
References 7 publications
28
344
6
6
Order By: Relevance
“…The material described here demonstrated a tensile modulus of 0.5 MPa, which was designed to cover the range of elastic response in normal healthy skin reported in the literature 24,25 . Such elastic recoil behaviour, together with a 250% elastic strain region until fracture demonstrated by this material, are likely design parameters that promote the seamless integration of the XPL at the skin interface, thereby allowing for even extreme ranges of motion while providing the instantaneous recoil that is characteristic of youthful, intact skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The material described here demonstrated a tensile modulus of 0.5 MPa, which was designed to cover the range of elastic response in normal healthy skin reported in the literature 24,25 . Such elastic recoil behaviour, together with a 250% elastic strain region until fracture demonstrated by this material, are likely design parameters that promote the seamless integration of the XPL at the skin interface, thereby allowing for even extreme ranges of motion while providing the instantaneous recoil that is characteristic of youthful, intact skin.…”
Section: Discussionmentioning
confidence: 99%
“…Three key mechanical design criteria in the development of the skin mimetic XPL required that the elastic recoil, flexibility, and elongation approximated the values of natural skin subjected to an initial elastic large deformation zone (strain under 40% and tensile modulus of 0.5-1.95 MPa) 25,26 . In Figure 1a, we report that the XPL maintained elastic recoil until break (fracture strain: 250 ± 82%) and the tensile modulus (0.51 ± 0.01 MPa) measured was comparable to that of natural skin.…”
Section: Mechanical Properties Of the Xplmentioning
confidence: 99%
“…where R is the approximated radius of the finger (16 mm, measured from the 25 year old female test participant), E is the Young's modulus of the finger (an average value of 0.49 MPa was used [30]), N is the normal load (in this case 11.7N), η is the dynamic viscosity (8.90×10…”
Section: "Liquid Bridges"mentioning
confidence: 99%
“…The lower the magnitude of Young's modulus the higher the contact area induced by the action of the capillary forces. Values of the Young's modulus of the stratum corneum vary greatly, depending on the water content of the stratum corneum [30]. Park & Badddiel [36,37] found in vitro the Young's modulus of skin (actually pig's ear, which is thought to be comparable to the human stratum corneum) to be approximately 1 GPa at 50% humidity and 3 MPa in water, however Agache et al [30] found it to be 2.1 MPa for the skin from a human back, at 22 °C and 82 % relative humidity.…”
Section: Capillary Adhesionmentioning
confidence: 99%
“…In contrast to intrinsically aged skin, which is characterised histologically by the loss of elastic fibre components, extrinsically aged skin is characterised by the gain of disorganised elastotic material. Despite these striking differences in ECM composition, the elastic moduli of both tissues are significantly increased compared with both young and UV-protected skin (Escoffier et al 1989;Agache et al 1980). It appears, therefore, that alterations in inter-or intra-molecular architecture, rather than ECM composition alone, must play a key role in mediating age-related loss of elasticity in the skin.…”
Section: Cutaneousmentioning
confidence: 99%